The Influence of Generation Y and Generation Z Human Resource Management Strategy on the Satisfaction and Commitment of Banking Employees in Makassar - Asriandi, Salim Basalamah, Ibrahim Dani; A.M. Hasbi (International Journal of Management Progress, 2021)
The purpose of this study is to empirically test and analyze the HR Management Strategy of Millennial Generation and Generation Z on employee satisfaction and commitment. The design of this study used a survey method with cross-sectional data collection through a questionnaire. Determination of the sample with non-probability sampling using two types of approaches, namely quota sampling and cluster sampling. The number of respondents is 100 employees each for the millennial generation and generation Z Banking in Makassar. The data analysis method used in testing the hypothesis is Structural Equation Modeling (SEM). The results provide evidence that the millennial generation and generation Z HR management strategies have a significant effect on satisfaction, the millennial generation HR management strategies have a significant effect on employee commitment but not for generation Z, millennial generation employee satisfaction has a significant effect on employee commitment but not for generation Z. satisfaction is an imperfect mediator in explaining the influence of millennial and generation Z HR management strategies on the commitment of banking employees in Makassar. The practical implication of this research is that it can provide an increase in employee understanding in increasing employee commitment through satisfaction which is influenced by the millennial generation and generation Z HR management strategies. millennial generation and generation Z on employee commitment by using satisfaction as a mediator of the relationship between variables, which previous research was mostly done partially.